Analisis Semiotika Hubungan Masyarakat (Humas) dalam Film “Cek Toko Sebelah” - Hafizur Kahfi Adnan; Elsa Tabina Siregar (Institut Nalanda, 2024)
The movie “Cek Toko Sebelah” directed by Ernest Prakasa, not only presents a family comedy-drama but also provides an in-depth look at public relations (PR) in a business context. Narrating the conflict between two brothers who must manage the family store while facing personal and professional challenges, the movie implies elements of image management, public communication, and customer relationship strategies. This research uses Ferdinand de Saussure's semiotic approach to analyze how semiotic elements in the film depict PR practices. Using qualitative and descriptive analytical methods, this research explores the meaning of signs and symbols in the film and their impact on the audience's understanding of PR. Data was drawn from the movie, script, critics' reviews, and related literature. The results show that the film conveys the conflict between modern and traditional values and changes in individual life priorities through visual and narrative elements, as well as how PR strategies shape the characters' perceptions and interactions with their environment.